Ecological Risk of the River Halda: A Perspective from Heavy Metal Assessment - Mohammad Ashraful Alam; Flura; Md. Anisur Rahman; Azhar Ali; Ahmed Ishtiaque Amin Chowdhury; Md. Hashibur Rahman; Md. Moniruzzaman; Md. Rahamat Ullah; Yahia Mahmud (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2022)
To evaluate the present status of heavy metals in the sediments of river Halda, seven heavy metals, viz. Cd, Cr, Cu, Fe, Mn, Pb, and Zn were assessed by Bangladesh Fisheries Research Institute by collecting data from 4 sampling locations (Khondokia Khal, Katakhali, Madari Khal, and Madarsha) and ecological risk impending from these metals were depicted from the study.  The concentration of heavy metals in the sediments of the river Halda ranged from 0.89-1.04 for Cd, 24.72-67.30 for Cr, 1.16-7.58 for Cu, 27899.31-60076.37 for Fe, 476.12-1137.20 for Mn, 0.77-8.33 for Pb and 40.33-121.77 mg kg−1 for Zn, respectively. The sediment geo-accumulation index (Igeo) values showed contamination only from two heavy metals Cd (1.10 ± 0.16) and Mn (1.48 ± 0.37). The average pollution load index (PLI) (0.37 ± 0.10) showed no marks of pollution in the studied sites, however; the mean degree of contamination factor (CF) showed moderate pollution. In the present study, the highest degree of contamination was observed at Katakhali (3.79 ± 2.07) followed by three other sites. The overall degree of contamination of four sampling sites was 2.68 ± 1.84 which indicated a low degree of contamination. The concentration of Cr ranged between 24.72-67.30 mg/kg with the highest (56.7 ± 9.4, mg/kg) at Madarshah and the lowest (30.2 ± 5.1, mg/kg) at Khondokia Khal. The highest concentration of Fe, Mn, and Zn (53926.3 ± 5338.2, 980.9 ± 145.1, and 108.0 ± 13.5 mg/kg) exhibited similar results to Cu and Pb; the maximum levels were found at Madarshah and the minimum levels (33571.1 ± 5456.0, 566.7 ± 92.8 and 56.0 ± 17.9 mg/kg) at Khondokia Khal, respectively. The enrichment factor (EF) (0.08 ± 0.02 to 4.16 ± 0) demonstrated none to moderate enrichment of the river. Nevertheless, the ecological risk factor (Eir) (17.83 ± 14.29 to 759.14 ± 192.26) and risk index (RI) (711.26 ± 122.55 to 1272.04 ± 175.19) exposed low to serious ecological risk for the river Halda.